Chloride anion templated synthesis and crystal structure of a handcuff catenane. - Evans, N; Serpell, C; Beer, P (2011)
Chloride, you're nicked! A novel handcuff catenane was prepared by anion templation and π-π stacking interactions. In addition, the first crystal structure determination of such a catenane is reported (see picture). Copyright © 2011 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.